Nontraditional media in marketing and advertising - Blakeman, Robyn, 1958- (Thousand Oaks, California : SAGE Publications, 2014)
'A concise guide that offers a step-by-step approach to the strategic use of alternative media by both the marketing and advertising professions. The text looks at why a marketing team might employ the use of alternative media vehicles over (or alongside) more traditional ones, how it can be used to attract smaller niche markets, and where alternative media is headed. Key features of this book include: Specific alternative media methods are discussed in separate chapters, including electronic and social media, mobile media, out-of-home and transit media, and direct marketing and sales. ; Numerous real-world case and visual examples are provided, including augmented reality, mobile GPS couponing, interactive television, cinema advertising, live mobile billboards, poster campaigns and many more. ; Checklists are included to provide students with a step-by-step guide to how to incorporate alternative media into future marketing campaigns. ; Critical thinking questions and exercises are provided to guide students in their own alternative media marketing efforts.'--Publisher's website.
Includes bibliographical references and index.
Keywords: Marketing; Advertising; Alternative mass media